Legal Policy on Changing the Nomenclature of the Ministry of State-Owned Enterprises to the State-Owned Enterprise Management Agency in Indonesia - Sinaga, Anna Shania de Zeta; Marsal, Irsyah (Rechtsvinding, 2025)
The reform of the governance of State-Owned Enterprises (BUMN) in Indonesia demands a fundamental separation of roles to balance the function of public service with an efficient and competitive corporate approach, as BUMN carries out the mandate of Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD NRI Tahun 1945). The previous dualism of functions between regulator and operator inherent in the Ministry of BUMN had hindered performance optimization and created the risk of political intervention, consequently triggering an urgent need to form entities focused on economic value and managerial independence. The establishment of the Danantara Investment Management Agency (BPI Danantara) as the operator holding and the BUMN Regulatory Agency (BP BUMN) as the regulator represents a strategic legal political policy aimed at eliminating moral hazard, enhancing accountability, and attracting global investment. This research employs a normative juridical method with statutory and conceptual approaches. The research results indicate that BPI Danantara is designated as the economic controller and business operator through majority share ownership, functioning as a professional fund manager responsible for value creation, restructuring, and the remediation of loss-making BUMN through a corporate cross-subsidy scheme. Conversely, BP BUMN plays the role of an independent regulator focusing on setting general policy directions, governance standards, and BUMN compliance oversight; however, the potential for conflicting authorities and the issue of meaningful participation in law formation must be addressed with robust check and balance mechanisms and highly detailed implementing regulations.